2022
DOI: 10.1101/2022.07.12.499744
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Characterising replisome disassembly in human cells

Abstract: To ensure faultless duplication of the entire genome, eukaryotic replication initiates from thousands of replication origins. Replication forks emanating from origins move through the chromatin until they encounter forks from neighbouring origins, at which point they terminate. In the final stages of this process the replication machinery (replisome) is unloaded from chromatin and disassembled. Work from model organisms has elucidated that during replisome unloading, the MCM7 subunit of the terminated replicat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 54 publications
0
4
0
Order By: Relevance
“…A similar back-up mitotic replisome disassembly pathway has now also been shown to exist in Xenopus laevis, mouse ES cells and human cells [66,68,98]. This pathway is capable of unloading replisomes at terminated or stalled replication forks and also relies on the same mechanisms/factors: ubiquitylation of MCM7 [98,99], CDC-48/p97/VCP unfoldase activity [64,68,98,99] and p97 cofactors NPL-4/UFD-1, as well as UBXN-3 in C. elegans [64], and UBXN7 and FAF1 in mouse ES cells [88] (Figure 5). Finally, while the evidence suggests that the SUMO protease ULP-4 supports this process in C. elegans [64], SUMOylation was found not to be required for the mitotic pathway functioning in X. laevis [98].…”
Section: Replisome Disassembly In Mitosis-the Back-up Pathwaymentioning
confidence: 70%
See 3 more Smart Citations
“…A similar back-up mitotic replisome disassembly pathway has now also been shown to exist in Xenopus laevis, mouse ES cells and human cells [66,68,98]. This pathway is capable of unloading replisomes at terminated or stalled replication forks and also relies on the same mechanisms/factors: ubiquitylation of MCM7 [98,99], CDC-48/p97/VCP unfoldase activity [64,68,98,99] and p97 cofactors NPL-4/UFD-1, as well as UBXN-3 in C. elegans [64], and UBXN7 and FAF1 in mouse ES cells [88] (Figure 5). Finally, while the evidence suggests that the SUMO protease ULP-4 supports this process in C. elegans [64], SUMOylation was found not to be required for the mitotic pathway functioning in X. laevis [98].…”
Section: Replisome Disassembly In Mitosis-the Back-up Pathwaymentioning
confidence: 70%
“…Experiments in C. elegans and X. laevis thus identified a Cullin ligase CUL-2 LRR−1 /Cul2 Lrr1 as a key protein recruited to chromatin at replication termination and confirmed that it was responsible for Mcm7 ubiquitylation [64,65]. More recent studies have now also confirmed CUL2 LRR1 to be needed for replisome disassembly in mouse stem cells and human cell lines [66][67][68] (Figure 3i). These latter studies demonstrated that the loss or depletion of LRR1 by CRISPR knockout, auxin-inducible degradation or siRNA impaired the ubiquitylation of MCM7 and led to the accumulation of replisomes on chromatin.…”
Section: Cullin Ubiquitin Ligases Driving Mcm7 Ubiquitylationmentioning
confidence: 74%
See 2 more Smart Citations